Effects of inoculation protocols on aroma profiles and quality of plum wine in mixed culture fermentation of Metschnikowia pulcherrima with Saccharomyces cerevisiae. (1st May 2022) - Zhang, Man; Zhong, Tao; Heygi, Ferenc; Wang, Zhirong; Du, Muying
Abstract: This study describes the first report of application of Metschnikowia pulcherrima combined with Saccharomyces cerevisiae to ferment plum wine. Variable factors studied include inoculum ratio ( M. pulcherrima: S. cerevisiae = 10:1, 1:1, and 1:10), as well as simultaneous versus sequential inoculation, with tested trials spanning 10:1sim, 1:1sim, 1:10sim, 10:1seq, 1:1seq, and 1:10seq, respectively. The yeast growth kinetics, physicochemical characteristics, organic acids, aroma profiles, and sensory evaluation were investigated. During fermentation, M. pulcherrima growth was inhibited by S. cerevisiae . Compared to each simultaneous analog, sequential fermentation which was inoculated with the same yeast ratio consumed less sugar and produced lower ethanol content. Organic acids in each sample varied with the use of different inoculation strategies. A total of 48 aroma compounds were quantified, and 1:1seq sample was observed to be abundant in esters and terpenes but relatively low in higher alcohols, fatty acids, and phenols. Sensory evaluation of the variously-prepared samples revealed that 1:1seq sample featured a highly intense 'global aroma', 'fruity', and 'alcohol' notes. PCA illustrated that different inoculation protocols of mixed culture fermentation influenced plum wine aroma except 1:10sim. Ultimately, 1:1seq was identified as a promising candidate for production of high-quality plum wine. Highlights: Metschnikowia pulcherrima was reported in plum wine at first time. Plum wines produced with varied protocols were evaluated. Sequential fermentation was more conducive to improve plum wine aroma and quality. 1:1seq is a good way for the improvement of fruity aroma in plum wine.